2018
DOI: 10.1016/j.ymthe.2018.07.023
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Exosome-Derived miR-130a Activates Angiogenesis in Gastric Cancer by Targeting C-MYB in Vascular Endothelial Cells

Abstract: Metastasis is a crucial reason for the poor prognosis of gastric cancer. Angiogenesis is closely associated with tumor invasion and metastasis. Cancer-derived exosomes play an important role in the establishment of the tumor microenvironment. In this study, exosomes were isolated by sequential differential centrifugation, and they were verified by transmission electron microscopy. Changes in the biological behavior of human umbilical vein endothelial cells were evaluated with downstream cellular functional exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 38 publications
2
121
0
Order By: Relevance
“…AML cells secrete angiogenic factors involved in vascular remodeling; however, antiangiogenic therapies do not improve AML patient outcome (Duarte et al, 2018), suggesting that AML cells *** *** *** Exosomes play a significant role in the establishment of the tumor microenvironment (X. Zhang, Yuan, et al, 2015) by shuttling oncogenic information that contributes to cancer spread (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…AML cells secrete angiogenic factors involved in vascular remodeling; however, antiangiogenic therapies do not improve AML patient outcome (Duarte et al, 2018), suggesting that AML cells *** *** *** Exosomes play a significant role in the establishment of the tumor microenvironment (X. Zhang, Yuan, et al, 2015) by shuttling oncogenic information that contributes to cancer spread (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of c-MYB correlated with higher grade ovarian cancer which suggested a direct relationship between c-MYB expression and aggressive ovarian cancer. The oncogenic role of c-MYB is not limited to ovarian cancer and has been reported in hematological malignancies as well as several solid tumors [9][10][11][12][13] , Despite such wealth of information regarding the oncogenic potential of c-MYB, its role in cisplatin resistance was not known prior to this report 9 . The study reported a connection between c-MYB expression and acquired cisplatin resistance, but there is still no clear understanding regarding how c-MYB can influence cisplatin resistance.…”
Section: Regulation Of Myb Mediated Cisplatin Resistance Of Ovarian Cmentioning
confidence: 96%
“…Emerging evidence indicates exosomal miRNAs mediate tumor‐associated angiogenesis. Yang et al . performed sequential differential centrifugation and identified that exosomal miR‐130a derived from GC cells could activate vascular cells via binding c‐MYB, indicated that miR‐130a drove angiogenesis (Table ).…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Emerging evidence indicates exosomal miRNAs mediate tumor-associated angiogenesis. Yang et al 47 performed sequential differential centrifugation and identified that exosomal miR-130a derived from GC cells could activate vascular cells via binding c-MYB, indicated that miR-130a drove angiogenesis (Table 1). Zeng et al 48 validated that miR-25-3p, a metastasis-promoting miRNA existing in CRC cells, could be transferred to endothelial cells via exosomes, regulated the expression of VEGFR2 by targeting KLF2 and KLF4, further contributed to increased vascular permeability and angiogenesis (Table 1 and Figs.…”
Section: Cancer Metastasismentioning
confidence: 99%